Flipped Classroom-Computer Based Instruction untuk Pembelajaran Pada Revolusi Industri 4.0: Rancang Bangun dan Analisis Kebutuhan - Sakti, Rizki Hardian; Sukardi, Sukardi; Giatman, Muhammad; Nazar, Ernawati; Wakhinuddin, Wakhinuddin; Waskito, Waskito (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
Technology has reached a level where today is a time for genuine educational reform that increases the achievement of student content by teaching lessons relevant to the industrial revolution 4.0. In the era of the industrial revolution 4.0, the challenges faced by education involved the cultivation of new technologies, because students were raised on new technologies so that they were impatient if they only filled out worksheets and listened to lectures, so that interesting media such as the Computer Based Instruction-Flipped Classroom were needed. The purpose of this study is to determine the needs analysis and design of the Computer Based Instruction-Flipped Classroom. The method used in this study is the SDLC (System Development Life Cycle) waterfall. The results of this study explain that the age of vocational students is in the range of 15 years to 18 years where vocational students are entering the stages of adolescent development. Characteristics of students at that age have a tendency to like contrasting colors, but not striking. Combining the components of color, music, and student creativity in learning with fun, it takes interesting media such as Computer Based Instruction-Flipped Classroom, as well as the design of Computer Based Instruction-Flipped Classroom using flowcharts, Unified Modeling Language (UML), which consists of designs use cases and sequence diagrams.